Marriage is Scary: Ketakutan Gen Z Terhadap Pernikahan di Era Modern - Abul Ala Al-Maududi; Ratu Mulya Hasasita; Fayola Nabila Putri; Dara Citra Persia; Zia Adzany Asher (Ikhlas : Jurnal Ilmiah Pendidikan Islam, 2026)
The "Marriage is Scary" phenomenon has been widely discussed by Generation Z across various social media platforms, reflecting a shift in perception and increasing anxiety toward marriage. This study aims to identify the factors triggering Generation Z's fear of marriage in the modern era and to review this phenomenon through the perspectives of Fiqih Munakahat (Islamic jurisprudence of marriage) and Fiqih Muamalah (Islamic jurisprudence of social and economic transactions). This qualitative study employs a literature review approach (library research), using primary sources from the Al-Qur'an, Hadith, and classical Fiqih books, alongside secondary data from relevant scientific journals. The findings reveal that Generation Z's fear of marriage is influenced by economic challenges, including the high cost of living and financial instability, widespread exposure to negative social media content, traumatic family experiences, inadequate mental and emotional readiness, and unrealistic expectations in choosing a partner. From the perspective of Fiqih Munakahat, this fear is considered a form of caution as long as it does not result in rejecting the sacred institution of marriage (mitsaqan ghalizha). Meanwhile, Fiqih Muamalah emphasizes honest, fair, and transparent financial management and the pursuit of lawful (halal) income rather than wealth accumulation. The study concludes that Islam offers comprehensive spiritual, mental, emotional, and financial preparation to help Generation Z view marriage as worship that brings sakinah, mawaddah, and rahmah.